Near Death Experience Dalam Perspektif Islam - Abdul Hadi (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2022)
Near death experience (NDE) is an experience that occurs related to death or the perception that death is coming. NDE can be caused by accidents, dreams, stress, sudden lack of oxygen, brain stimulation and coma. This study aims to understand the relationship between NDE events in an Islamic perspective. The data collection method is library study from journals, books, internet, documentation and libraries. NDE is a condition in which the patient has not yet died. Patients with NDE experience anomalies in the nervous system, abnormalities or disturbances in the results of scanning performed by a neurologist or neuroscientist. NDE in the Islamic perspective believes that every individual at the right time will experience death. Suspended death in Hadith Qudsi is defined as a door that connects the world and the hereafter. The principle of suspended animation is the same as for people who are sleeping, namely the spirit is likened to a rope that has two ends tied to the body. If one end of the rope is separated from the body, it allows humans to float or it is called a dream / suspended animation. Therefore, discussing NDE in an Islamic perspective, it is necessary to have a deeper understanding so that Muslims can understand the definition of death based on science and Islamic science so that it does not raise any doubts.